Design and Implementation of the Control System of an Internal Combustion Engine Test Unit. (10th February 2014) - Koç, Tufan; Karayel, Durmuş; Boru, Barış; Ayhan, Vezir; Cesur, İdris; Parlak, Adnan
Abstract : Accurate tests and performance analysis of engines are required to minimize measurement errors and so the use of the advanced test equipment is imperative. In other words, the reliable test results depend on the measurement of many parameters and recording the experimental data accurately which is depended on engine test unit. This study aims to design the control system of an internal combustion engine test unit. In the study, the performance parameters of an available internal combustion engine have been transferred to computer in real time. A data acquisition (DAQ) card has been used to transfer the experimental data to the computer. Also, a user interface has been developed for performing the necessary procedures by using LabVIEW. The dynamometer load, the fuel consumption, and the desired speed can easily be adjusted precisely by using DAQ card and the user interface during the engine test. Load, fuel consumption, and temperature values (the engine inlet-outlet, exhaust inlet-outlet, oil, and environment) can be seen on the interface and also these values can be recorded to the computer. It is expected that developed system will contribute both to the education of students and to the researchers' studies and so it will eliminate a major lack.